Dispersed repeats and inverted repeat expansion drive major plastomic rearrangements in Calliandra haematocephala (Leguminosae: Mimoseae) - Zhao, Libo; An, Kailun; Gu, Wei; Lu, Qing; Wang, Ding-Jie; XiaHou, Zuoying; Zhang, Rong; Yi, Ting-Shuang (Frontiers in Plant Science, 2025)
Structural variations in legume plastomes impact phylogenetic and evolutionary studies. In this study, we focus on the tribe Mimoseae by integrating a newly assembled plastome of Calliandra haematocephala (from PacBio sequencing data) with 15 previously published plastomes representing major lineages, to analyze structural rearrangements, repeat sequences, and selection pressures. The plastome of C. haematocephala revealed extensive structural rearrangements and a ca. 14-kb expansion of the inverted repeats (IRs) into the large single copy (LSC) region, resulting in IRs of 42,069 bp. It also contained a high abundance of clustered dispersed repeats (> 90 bp). These features potentially contribute to significant plastome rearrangements, making it the largest plastome (200,623 bp) recorded to date in Mimoseae and, more broadly, in Leguminosae. Nucleotide diversity (Pi) analysis identified several highly variable regions (Pi > 0.03), including the genes accD, rps18, clpP, and multiple non-coding loci, suggesting their potential as molecular markers. Selection pressure analyses detected positive selection (dN/dS > 1) in clpP, ycf2, and rps17, suggesting possible roles in adaptive evolution. Branch-specific positive selection was also found in genes such as rpoC1 and atpA within the Calliandra clade, indicating lineage-specific adaptive pressures. This study highlights the dynamic evolution of plastomes in Mimoseae and offers new insights into their structural diversity and adaptive evolution.